Collective Design Network: Systems Thinking (Event-Pattern-Structures) and System Dynamics Modelling as a Design Concept and Strategy - Kozikoglu, Nilufer; Erdogan, Meral; Nircan, Ahmet Kutsi; Akipek, Fulya Ozsel (ECAADE-EDUCATION & RESEARCH COMPUTER AIDED ARCHITECTURAL DESIGN EUROPE, 2009)
This paper will relay the initial phase of a collaborative work within partners from the design discipline, systems engineering, and software engineering which deals with the interrelations of network idea, systems thinking, collective design, and computation. Vensim-a system dynamics modelling tool developed by Ventana Systems, Inc. in 1992 - has been used in an experimental first year design studio to engage students in systems thinking in the architectural design environment. It has been observed that this tool enabled most students to develop a multi-layered, complex and more controlled design logic and to amplify the cognitive processes at the beginning of the design education. We conclude that in order to fully realize systems thinking in the design process, new ways of integrating parametric design environments and system dynamic modelling environments needs to be investigated.
Keywords: Design network; system dynamics; dynamic pattern; collectivity; integration; Architecture